SEISMOGEODYNAMIC FACTOR IN TRIGGERING OF DEBRIS FLOWS ON THE SOUTHERN SLOPES OF THE KODAR RIDGE - V. K. Laperdin; V. A. Sankov; A. A. Dobrynina (Геодинамика и тектонофизика)
Potential triggering of mudflows by geodynamic and seismotectonic factors was assessed for the NE flank of the Baikal rift system, specifically for the junction area of the SW segment of the Chara depression, the Kodar ridge and the Muya-Chara inter-basin zone. The debris flow hazard in the study area is high due to geodynamic and seismotectonic activity and the regional permafrost, hydrological and climatic conditions. In 2001, debris flow damaged the railway section of the Baikal-Amur Mainline (BAM) on the northern shore of the Bolshoe Leprindo lake. To ensure stable railway operations, BAM must be protected from landslides and debris flows. Appropriate preventive actions need to be developed with respect to the correctly assessed current state of the local natural environment, which results from complex interactions between endogenous and exogenous processes. In our study, the Late Cenozoic geodynamics, faulting and seismicity are considered as the most important factors for the occurrence of landslides and mudflows on the southern slopes of the Kodar ridge. The relief in the study area develops in geodynamic conditions predetermined by active stretching of the crust, accompanied by uplifting of the rift shoulder with a large height gradient. The study area is a narrow segment of the zone of dynamic influence of the Baikal rift system. It has a dense network of faults activated in the Late Cenozoic and the fault segments active in Holocene, as deformation caused by the divergent movements of the Siberian and Transbaikalia lithospheric blocks concentrates in this narrow zone. We studied several fault systems, including those activated in the Late Cenozoic, which are related to abundant zones of high fracturing, fragmentation and disintegration of rocks to dust-size particles, accompanied by the most intensive physical weathering in such zones. In the Chara depression and the surrounding uplifts, modern seismicity and paleoseismicity are determined by differentiated movements along the active faults. In the modern and Holocene stages, during and after frequent seismic shocks (including strong ones) in the study area, loose debris materials are intensely displaced by gravity, accumulate in negative-relief forms, and provide an important source of solids for debris flows. The Stanovoi Plateau is currently experiencing a period of intensified tectonic and seismic activity, which contributes to favorable conditions for the occurrence of mudflows.